Vertical profiles of cobalt and zinc in marine sediments of the Santa Rosalía mining region, Gulf of California, Mexico. - Shumilin, E.; Rodríguez Figueroa, G.; Sapozhnikov, D.; Mirlean, N. (Journal of Iberian Geology, 2013)
Core sediments that were sampled from the coastal zone of the Santa Rosalía mining region and the adjacent deeper area of the Gulf of California were analysed by an instrumental neutron activation analysis (INAA). The levels of Co, Sc and Zn were used to assess the effect of pollution from the solid wastes of a copper smelter on the sediment composition in the study area. The Co/Sc and Zn/Sc ratio vertical distributions were compared to Co/Sc and Zn/Sc ratios of the earth’s crust and to a lower layer of the sediment cores and therefore less affected by pollution. The ratios of Co/Sc and Zn/Sc in cores from a predominant pollution “hot spot” near Santa Rosalía port are very high (40-150 and 150-350, respectively), suggesting that the thickness of the polluted layer exceeded the length of the cores (75-93 cm). The values of Co/Sc and Zn/Sc ratios decrease drastically in the cores collected outside the main “hot spot”. In this case, the values obtained from core depths of 20-34 cm approached the regional coastal surface sediment background (approximately 2 and 5-10 for Co/Sc and Zn/Sc, respectivelly). The Co/Sc ratios for the sediments of the deeper and further from the coast cores are slightly variable, but at sediment depths below 15 cm they are nearly constant and approximately equal to the Co/ Sc ratio of the earth´s crust. In the upper part of these cores (0-15 cm), the Zn/Sc ratios are higher (10-20) than the Zn/Sc ratio of the earth´s crust, which was probably due to the additional input of incompletely mineralised biogenic particulate Zn from the photic layer of the water column. The shape of the vertical profile the Zn/Sc ratio of SR22 sediment core (depth 360 m) in front of the main pollution “hot spot” shows that the maximum levels of pollution occurred in the past, and self-purification/restoration of the natural pollutant levels in the fine deep-water sediments can be observed during recent years.